Indoor air quality improvement in natural ventilation using a fuzzy logic controller - Kulis Cezary; Müller Jarosław (Technical Transactions, 2020)
The aim of the research was to design and validate the prototype of a device developed to improve the quality of indoor air by supporting the natural ventilation in building. A CO2 sensor and thermo-hygrometer were used to measure the physical parameters of the indoor air. The developed device is based on the Raspberry Pi single-board-computer (SBC) and optical sensors. The prototype casing was made using 3D printing technology. The software was written using the Python 2.7 programming language. The key algorithm of control uses fuzzy logic. The effectiveness of the developed device has been confirmed. The use of the device enabled improvement of the indoor air quality. The presented device may be a solution to improve the indoor air quality by supporting the ventilation system.